Clinical effectiveness of symptomatic therapy compared to standard step up care for the treatment of low impact psoriatic oligoarthritis: the 2-arm parallel group randomised POISE feasibility study - Rombach, I; Tucker, L; Tillett, W; Jadon, D; Watson, M; Francis, A; Sinomati, Y; Dutton, SJ; Coates, L (SAGE Publications, 2022)
Introduction In psoriatic arthritis (PsA), treatment recommendations support first line use of disease-modifying anti-rheumatic drugs (DMARDs). There are few treatment strategy trials and no previous studies have investigated tailored treatment choice by disease severity. Studies in oligoarthritis (<5 inflamed joints) are limited but have suggested that some can be managed without DMARDs, preventing unnecessary side effects. This study aimed to assess the feasibility and acceptability of a study comparing standard DMARD treatment against symptomatic therapy in patients with mild psoriatic oligoarthritis.